Interactions of epitopic variants of epidermal growth factor receptor with therapeutic anti- EGFR antibodies - Mahdiyah, SU; Ahsan, T; Fatema, K; Shoily, SS; Sajib, AA (Dhaka University Journal of Biological Sciences, 2022)
Epidermal growth factor receptor (EGFR) plays important roles in cancerous transformation of epithelial cells in many solid cancers. Due to the pivotal role of EGFR in cellular proliferation and metastasis, it is a promising molecular target for the treatment of various cancers. One of the major treatment approaches uses anti-EGFR monoclonal antibodies (mAbs) targeted to the extracellular domain of the receptor to competitively block the binding of its ligands. Cetuximab, necitumumab, nimotuzumab, and panitumumab are such approved mAbs which are commercially available and used to treat multiple types of cancers. The response rates to these expensive therapeutics in various cancers range from nearly 9% to 91%. Hence, the objective of this study was to indentify whether any of the missense single nucleotide polymorphisms (SNPs) in the EGFR gene impart any structural and functional impact on the receptor’s interaction with these antibodies. We used X-ray crystallographic structures (from Protein Data Bank) of the Fab fragments of these therapeutic antibodies in complex with EGFR to analyze the effects of the missense mutations on the antigen-antibody interactions. We also assessed the potential association of the destabilizing variants with pathogenicity and disease susceptibility. EGFR H433Q (rs1171743336), S464T (rs746763556), S492G (rs1057519760) and S492R (rs1057519860) variants appear to weaken interactions between EGFR and cetuximab, which is the most widely used anti-EGFR therapeutic antibody. Other epitopic variants do not appear to affect interactions between EGFR and relevant mAbs (necitumumab, nimotuzumab, and panitumumab). Prior to treatment of the EGFR mediated conditions with cetuximab, screening of variants that destabilize antibody-EGFR interaction may be considered as a companion diagnostic test for avoiding unresponsiveness and improving therapeutic outcomes. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 393-403, 2022 (June)